Demodex mites modulate sebocyte immune reaction. (24th August 2018) - Lacey, N.; Russell‐Hallinan, A.; Zouboulis, C.C.; Powell, F.C.
Summary: Rosacea is a common skin condition affecting the face – most commonly of middle‐aged adults ‐ that results in redness and pimples, which can cause much embarrassment for the patient. The cause of rosacea is unknown but there is strong evidence that numbers of the microscopic skin mite called Demodex folliculorum are greatly increased in the facial skin of patients with rosacea. What role this imbalance in numbers of mites may play in the skin and development of rosacea has been unexplained to date and how they interact with our immune system has not been shown previously. We were able to demonstrate, for the first time, that live Demodex mites had the capacity to increase or decrease the inflammatory response in cells found in the oil glands of facial skin (called sebocytes) when these mites were cultured together with those cells in the laboratory. The numbers of mites that were co‐cultured with the cells influenced the type of response elicited by the cells. Increased mite numbers caused a pro‐inflammatory reaction. This new information helps us to understand the capacity of Demodex mites to interact with cells in the skin. It helps us to understand how, in low numbers, mites can reside in normal skin by blocking an inflammatory response by cells. It also gives us insight as to how increased numbers of Demodex mites may induce a different response from cells resulting in inflammation. This research provides us with a possible mechanism linking increased numbers of mites in the skin with the development of rosacea. Abstract : Linked Article:  Lacey et al. Br J Dermatol 2018;179 :420–430